2005
DOI: 10.4028/www.scientific.net/msf.483-485.97
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Basal Plane Dislocations in the 4H-SiC Epilayers Grown on {0001} Substrates

Abstract: In this paper, we investigated the density of basal plane dislocations (BPDs) in 4H-SiC epilayers grown on (0001) and (000-1). Re-polishing of the substrate surface, in-situ H2 etching and off-cut angle were found to influence the propagation of BPDs into the epilayers. The epitaxial growth on (000-1) substrates yields a relatively low density of BPDs compared to growth on (0001). The electrical characteristics of pn diodes were also investigated, and the suppressed forward degradation and high-voltage blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…More recently, Stahlbush et al reported the reduction of BPD density in epitaxial growth on 8° off substrates by using growth interrupts in the growth process [48]. In our earlier paper, we reported the advantage of using 4° off (or 3.5° off) substrates in terms of reducing BPDs in the epilayer in a comparison with using 8° off substrates [49], while we did not distinguish BPDs with a 1/3〈1120〉-type Burgers vector and basal plane Frank partials with a 1/4[0001] Burgers vector at that time. Chen and Capano confirmed the advantage of 4° off substrates to reduce BPDs in the epilayer [50].…”
Section: Featurementioning
confidence: 93%
“…More recently, Stahlbush et al reported the reduction of BPD density in epitaxial growth on 8° off substrates by using growth interrupts in the growth process [48]. In our earlier paper, we reported the advantage of using 4° off (or 3.5° off) substrates in terms of reducing BPDs in the epilayer in a comparison with using 8° off substrates [49], while we did not distinguish BPDs with a 1/3〈1120〉-type Burgers vector and basal plane Frank partials with a 1/4[0001] Burgers vector at that time. Chen and Capano confirmed the advantage of 4° off substrates to reduce BPDs in the epilayer [50].…”
Section: Featurementioning
confidence: 93%
“…Recently, 0 0 01 C-face 4H-SiC epitaxial growth has gained some attention due to a few advantages over Si-face. Low basal plane dislocation (BPD) densities are reported on epilayers grown on C-face 4H-SiC substrate [1,2]. As a result, high-voltage pin diodes fabricated on C-face show superior forward voltage stability compared with those on Si-face [3,4].…”
Section: Introductionmentioning
confidence: 97%
“…The BPD density in epilayers was drastically reduced by using smaller off-cut angle substrates. [19][20][21][22] By using 4 • off-cut substrates, a 97-100% conversion rate was reported without pre-growth treatments or growth interrupts. 23 Since the very low BPD density (0.09 cm −2 ) was also achieved without particular pretreatment in this study, the use of 4 • off-cut substrates may be an essential approach to realize nearly 100% conversion rate of BPDs to TEDs.…”
Section: Resultsmentioning
confidence: 99%